Pregnant Women’s Knowledge and Attitudes toward Epidural Anesthesia in Saudi Arabia: Pharmaceutical Science-Obstetrics for better Mother health - Zaidyah N. Zaihi; Laila M. Harbi; Nidaa S. Jaylan; Aisha A. Qumiri; Zahra M. Alsrori; Najla M. Asheeri; Fatimah A. Abudyab; Eshraq E. Othman; Athar M. Madkhali; Raniyah A. Ahmed (International Journal of Life Science and Pharma Research, 2022)
Labor pain is one of the most severe forms of pain a woman can endure throughout her lifetime. Epidural anesthesia (EA) is a widely used and effective method of analgesia for labor pain. If administered timely, EA relives about 90% to 95% of the labor pain. The objective of this study was to evaluate the knowledge and attitudes toward EA in a sample of pregnant women from Jazan region, Saudi Arabia. We conducted a cross-sectional study on a sample of 172 pregnant women using an online survey. Socio demographic data and responses to the questions about knowledge and attitudes toward EA were analyzed using descriptive tests and Chi-square test. The mean age of participants was 27.8 ± 6.3 years. About 46.5% of respondents had a university degree and 39.5% had finished high school. Overall, women showed adequate knowledge about EA and 36.6% had positive attitudes toward the use of EA for labor pain. The factors that were significantly associated with positive attitudes were education (χ2: 24.98, P<0.05), parity (χ2: 22.93, P<0.05), past experience with EA (χ2: 32.24, P<0.001), and source of knowledge (χ2: 19.61, P<0.05). This study revealed adequate knowledge about EA among pregnant women. More than one-third (36.6%) showed positive attitudes toward using EA. Significant factors affecting attitudes toward EA were high education, multiparty, experience with EA, and source of information about EA. Implications and recommendations are discussed.